A Modeling Framework for Maintenance Optimization of Electrical Components Based on Fuzzy Logic and Effective Age. (16th March 2012) - Baraldi, P.; Balestrero, A.; Compare, M.; Benetrix, L.; Despujols, A.; Zio, E.
<x xml:space="preserve">Abstract</x> In this article, the problem of building a model in support of maintenance optimization when the only available information is that elicited from one expert is tackled. In particular, the degradation process affecting the component is modeled by resorting to the concept of effective age. Information is elicited from one expert by following a systematic literature approach, and the theoretical framework of fuzzy logic is used to deal with his or her qualitative statements. A hybrid approach based on Monte Carlo method and fuzzy logic is then applied to evaluate the performance of a given maintenance policy. Finally, the proposed methodology is applied to a real case study dealing with a medium‐voltage test network. Copyright © 2012 John Wiley & Sons, Ltd.